Auditoría administrativa al sindicato de choferes profesionales del cantón Quevedo. periodo 2012 - Pasquel Cadena, Johanna Mabel (2014)
This research was conducted in the city of Quevedo - Province of Los Ríos , who had the same goal to run a Management Audit of the Union of Professional Drivers of Canton and verify the level of compliance of the Organic Statute , Administrative Procedures Manual , Rules of Procedure , objectives, plans and programs of the institution, its organizational and functional structure , controls , personnel and facilities of the organization, according to terms of efficiency, effectiveness and efficiency . The methodological tools used in the development of the Management Audit were direct observation, questionnaire survey and internal control partners and interview Drivers Union directive which allowed to identify the main being experienced by the institution. Among the findings are detected the absence of a manual functions and procedures, compliance programs and plans established by the institution and lack of performance evaluation to its employees. The results of the implementation of internal control questionnaire yielded a confidence level of 66.33 % considered moderate to good , which allowed us to evaluate the efficiency , effectiveness and economy concluding that certain activities in the Bank are not performed properly, but the union generally has a good administration.